IMPLEMENTASI PENGELOLAAN KEUANGAN BADAN USAHA MILIK DESA (STUDI DESA GONDOWANGI KECAMATAN WAGIR KABUPATEN MALANG) - Rofidah, Naily; Rochayatun, Sulis (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Village development is the focus of national development because the village is a sub-section of the national territory that directly manage the society. Nowdays villages are required to have BUMDes as a leading organization aimed to optimize village potential (Wargiyat, 2015). The management of BUMDes must be in accordance with established regulations; financial management of BUMDes is guided by Regulation of The Minister of Village (Permendes) Number 4 of 2015 and Ministry of Home Affair regulations (Permendagri) 113 of 2015. Principles that must be upheld in the management of BUMDes are cooperative, participatory, emancipatory, transparent, accountable, and sustainable.The purpose of this study is to determine the financial management of BUMDes Gondowangi in Gondowangi Village, Wagir District, Malang Regency. The type of this research is qualitative with a case study approach. The conclusions that can be taken are financial management carried out by BUMDes Gondowangi is still simple. The planning is done by holding a meeting of each unit to form the budget plan (RAB). Implementation is carried out using receipts as proof of disbursement of funds. However, the administration is done by recording cash income and expenditure. Then, Recording which is carried out is still general. Accountability is carried out by giving a report to the regional consultative committee (BPD) of Village and Community and Village Empowerment and Service (DPMD) of Malang District, as well as sending a soft file to the Ministry of Village, and delivering it to the community together with the village meeting. The accountability of regular activities in 2017 is also carried out by BUMDes Gondowangi in village meetings. Supervision in the form of guidance from the governor and regent / mayor has not been obtained by BUMDes Gondowangi.Â